COMPARATIVE STUDY BETWEEN THE USE OF SONGS AND FLASHCARDS TO INCREASE STUDENTS’ VOCABULARY MASTERY - Sunarti, Sunarti; Mudi, Nabila Putri; Halim, Abdul; Puspita, Rani Herning Puspita (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The aim of this research is to compare the use of songs or flashcards which can increase students' vocabulary significantly and which are more effective in increasing students' vocabulary.The research method used is quantitative with experimental research type. The research subjects were class X students of Samarinda State High School. Class X consists of 5 classes and each class consists of 20 students, and the total sample in this study was 40 students. This research was conducted in 6 sessions which included pre-test and post-test. After the four treatment periods were completed, a post-test was carried out. The data collection tool used was English questions that focused on vocabulary.The research results showed that in the first test, the class filled with songs had an average score of 19.5. The average score of students who were taught with flash cards was 20.7. In the second test, the average score of students who were taught songs was 20.15. Meanwhile the average class processed with flashcards was 22.45. This proves that flashcard media is better in improving English vocabulary mastery.